Estimation of Heavy Metal Concentrations in the Water of Urban Lakes in the Russian Arctic (Murmansk) - Postevaya, Marina A.; Slukovskii, Zakhar I.; Dauvalter, Vladimir A.; Bernadskaya, Daria S. (Water (Basel), 2021)
This article presents the results of the analysis and estimation of the seasonal variation of heavy metals in the water of urban lakes and the assessment of their environmental state based on the chemical data. The research covered seven lakes in Murmansk, subject to various levels of anthropogenic load. Field studies were conducted in 2019–2020. Water samples were taken both in summer and in winter/spring seasons. The most polluted lake was Lake Ledovoe, where the highest concentrations of V, Cr, Co, Ni, Cu, W, and Mn were found. Lake Yuzhnoe, which is characterized by the lowest concentrations of studied heavy metals, was the least subject to anthropogenic load. In total, V, Ni, Zn, Fe, and Mn were above the background levels in the lakes of Murmansk. The analysis of the seasonal variation showed that the highest concentrations of heavy metals were found in winter/spring season and reached their maximum during the period of melt water intake from the catchment area. The research showed the impact of the urban environment on the chemical composition of the Murmansk lakes.